(3cJGH aj GdCSHGH GdeGScIs - (3LGdjfhSs ((3Nda Hf CHj GdQHjY GdCfOdSi s)
(3ChdgG (B:s
(3Cf Chd ef YdeJg bGd SHHkG eGSckG ef GdadGSaI CUMGH GdeXdI s
(3BNQgG (B:s
(3hPdc Efc hEf SejJ MGdGf GdHOf CeQGVkG aEfc JaYd eKd eG jaYd ef jSejgG CSHGHkG ddCeQGV JeJ ebGdI LGdjfhS s
(3Vef eLehY , JQJjHgG (B: (3GdebGdI GdSGHYIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs